Effects of 4d transition metal Pd doping on the magnetic and superconducting properties of 112-type iron pnictide EuFeAs2. (29th December 2021) - Zhan, Xinhui; Yi, Xiaolei; Xing, Xiangzhuo; Li, Meng; Yu, Linchao; Huang, Song; Feng, Jiajia; Meng, Yan; Zhou, Nan; Liu, Xiaobing; Shi, Zhixiang
Abstract: The recently discovered 112-type EuFeAs2 compound that shows complex Eu-spin magnetism provides a new platform to study the interplay between superconductivity (SC) and magnetism in iron pnictide superconductors. In this paper, by substituting Fe with the 4 d transition metal (TM) Pd, we have synthesized a series of EuFe1− x Pd x As2 (0 ⩽ x ⩽ 0.08) samples and studied the doping effect on SC and magnetism by means of electrical transport and magnetization measurements. The systematic evolution of the lattice parameters indicates that the Pd atoms have been successfully substituted into the Fe sites. With Pd doping, the Fe-related spin density wave transition at T m Fe in the parent phase is rapidly suppressed, and SC simultaneously emerges, exhibiting a domelike shape with a maximum onset transition temperature T c onset of around 18.5 K at x = 0.04. On the other hand, the Eu-related antiferromagnetic order at T m Eu is suppressed very slowly and persists up to x = 0.08, covering the whole SC dome region. Also, the reentrant spin-glass and spin-reorientation transitions below T m Eu remain unchanged with Pd doping. All these results indicate that the Eu spins have little effect on SC in EuFe1− x Pd x As2 . Finally, based on the resistivity and magnetization data, the T − x phase diagram of EuFe1− x Pd x As2 is constructed and compared with those of 3 d TMs Co/Ni and La doped ones.